2008
DOI: 10.1002/ejic.200800570
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal Dilution on the Light‐Induced Spin Transition in Two 1D Chain Compounds: [FexZn1–x(btzp)3](BF4)2 and [FexZn1–x(endi)3](BF4)2 {btzp = 1,2‐Bis(tetrazol‐1‐yl)propane and endi = 1,2‐Bis(tetrazol‐1‐yl)ethane}

Abstract: Keywords: Iron / Magnetic properties / Spin crossover / Photomagnetism / Dilution effectsThe thermal and light-induced spin transitions in [Fe x Zn 1-x -(btzp) 3 ](BF 4 ) 2 and [Fe x Zn 1-x (endi) 3 ](BF 4 ) 2 {btzp = 1,2-bis-(tetrazol-1-yl)propane; endi = 1,2-bis(tetrazol-1-yl)ethane} chain compounds have been investigated by magnetic susceptibility, photomagnetism and diffuse reflectivity measurements. These compounds display a thermal spin transition and the Light-Induced Excited Spin State Trapping (LIESST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Such defects are known to result in more gradual SCO natures as well as resulting in increased HS residual fractions at low temperature, as commonly observed in past reports on the effect of grinding SCO materials into finer particles and for metal dilution studies. [13,23] Indeed, a more gradual SCO nature has also been observed in nanoparticle preparations of the polymeric system Fe(pyrazine){Pt(CN) 4 } and in this report it was suggested that this is caused by the peripheral iron(II) sites not undergoing SCO. [1,8] These effects would also contribute to the observed loss of two-step nature.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Such defects are known to result in more gradual SCO natures as well as resulting in increased HS residual fractions at low temperature, as commonly observed in past reports on the effect of grinding SCO materials into finer particles and for metal dilution studies. [13,23] Indeed, a more gradual SCO nature has also been observed in nanoparticle preparations of the polymeric system Fe(pyrazine){Pt(CN) 4 } and in this report it was suggested that this is caused by the peripheral iron(II) sites not undergoing SCO. [1,8] These effects would also contribute to the observed loss of two-step nature.…”
Section: Discussionmentioning
confidence: 77%
“…[23][24][25] In Figure 6 we show purely for comparative purposes the results of a previously reported metal dilution study on the material [Fe x Mn 1-x (bpp) 2 ](NCSe) 2 [bpp = 2,6-bis(pyrazol-3-yl)pyridine] to highlight the similarities with the current micellar preparation study. Of particular note is the more gradual spin transition, greater residual HS fraction and decreased transition temperatures with increasing SCO metal dilution.…”
Section: Discussionmentioning
confidence: 94%
“…[13] For example, a recent metal-dilution study on [Fe 0.02 Mn 0.98 (terpy) 2 ](ClO 4 ) 2 (terpy = 2,2Ј;6Ј,2"-terpyridine) has shown that although the iron complexes remain in the LS state when incorporated into the lattice of the corresponding manganese(II) complexes, they can flip to the HS state by irradiation of the dilute phase at low temperature. [14] The metastable HS state undergoes thermal relaxation to the LS state at elevated temperature, but very long lifetimes have been observed (i.e., several days) when T Ͻ 20 K. Many metal-dilution studies focused on studying the light-induced excited state spin trapping (LIESST), [15][16][17] but there are, to the best of our knowledge, very few metal-dilution studies on the temperature-induced SCO of two-step mononuclear compounds.…”
Section: Introductionmentioning
confidence: 99%
“…T(LIESST) is obtained by the inflexion point position of the derivative of the χ M T vs T plot (χ M stands for the molar magnetic susceptibility) recorded after light irradiation [34][35][36]. This temperature, obtained after warming at a given temperature scan rate, was shown to be constant [28,29,37,38] or slightly increased [39][40][41] upon metal dilution.…”
Section: Introductionmentioning
confidence: 99%